Skill and Strategy: How Managerial Ability Drives Working Capital Efficiency [version 1; peer review: 2 approved, 1 approved with reservations] - Sagar Bhatt; Prasenjit Roy; Asokan Vasudevan; Elangbam Nixon Singh; Premendra Kumar Singh; Rakesh Dani (F1000Research)
Background The study investigates the impact of Managerial Ability (MA) on Working Capital Management Efficiency (WCME), focusing on how skilled management influences working capital practices. It also explores the variation in this relationship across firms with different characteristics such as profitability and market valuations within India’s economic landscape. Methods Using a balanced panel dataset of 150 listed companies from the National Stock Exchange (NSE) of India for the period 2014–2023, the study employs Data Envelopment Analysis (DEA). WCME is assessed as a multidimensional efficiency metric incorporating inventory, accounts receivable, accounts payable, cost of goods sold , net revenue, and net income. MA is estimated using a two-step DEA-based approach, separating managerial ability from firm-specific characteristics. Generalized Estimating Equations (GEE) regression models are applied to examine the individual and interactive effects of MA and Tobin’s Q (TBQ) on WCME along with other important variables. Results The results demonstrate that MA significantly enhances WCME, particularly in firms with lower TBQ. The analysis also reveals that skilled managerial characteristics amplifies the efficiency of working capital management, aligning with the Upper Echelon Theory's (UET) claim that managerial attributes play a critical role in organizational efficiency. Conclusion The study demonstrates managerial ability has a strong influence on corporate working capital policies. This advocates prevalence of certain fundamental concepts such as viz. Upper Echelon Theory (UET), Resource-Based View (RBV), and Agency Theory (AT). From managerial point of view, it is suggested to adopt strategic approaches in practicing WCME that will enhance firm’s competitive advantage and long-term sustainability.